Correction: MOF-derived PtCo/Co3O4 nanocomposites in carbonaceous matrices as high-performance ORR electrocatalysts synthesized via laser ablation techniques. Issue 4 (8th February 2021) - Ribeiro, Erick L.; Davis, Elijah M.; Mokhtarnejad, Mahshid; Hu, Sheng; Mukherjee, Dibyendu; Khomami, Bamin
Abstract : Correction for 'MOF-derived PtCo/Co3 O4 nanocomposites in carbonaceous matrices as high-performance ORR electrocatalysts synthesized via laser ablation techniques' by Erick L. Ribeiro et al., Catal. Sci. Technol., 2021, ; DOI: 10.1039/d0cy02099k .